Combustion duration influence on hydrogen-ethanol dual fueled engine emissions: An experimental analysis - Syed Yousufuddin (National Research and Innovation Agency, 2018)
The research presented in this article expresses experimental results on combustion duration effect on the dual fueled engine. In particular, the research was focused on the emissions occurred specifically from a hydrogen-ethanol dual fueled engine. This study was performed on a compression ignition engine that was converted to run and act as a spark ignition engine. This modified engine was fueled by hydrogen–ethanol with various percentage substitutions of hydrogen. The substitution was altered from 20 to 80% at a constant speed of 1500 rpm. The various engine emission characteristics such as CO, Hydrocarbon, and NOx were experimentally determined. This study resulted that at a compression ratio of 11:1 and combustion duration of 25°CA, the best operating conditions of the engine were shown. Moreover, the optimum fuel combination was established at 60 to 80% of hydrogen substitution to ethanol. The experimental results also revealed that at 100% load and at compression ratios 7, 9, and 11; the CO and HC emissions have decreased while NOx increased and followed with the increase in the percentage of hydrogen addition and combustion duration. It was concluded that the retarding combustion duration was preferred for NOx emission control in the engine.